Commissariats of Military Industry during the Great Patriotic War - Yu. V. Il’In (Vestnik MGIMO-Universiteta)
Strengthening national defense by building up military and economic potential was the most important vital task of the Soviet Union during the whole period of its existence. The price of enormous effort of labor, research and design teams, huge material and financial costs in the course of the prewar five-year plans in the Soviet Union was paid and incurred to create the military-industrial complex (MIC) - sector of social production, designed to provide security for the state in armed struggle. The core of the DIC were four industry: Commissariat of Aviation Industry (NCAP), the People’s Commissariat of ammunition (NBC) weapons Commissariat (IEC) and the People's Commissariat of the shipbuilding industry (NCSP), formed in accordance with the Decree of the Presidium of the Supreme Soviet on January 11, 1939 by separation of the People's Commissariat of Defense Industry of the USSR. They became a separate group of central government, designed to provide measures for the implementation of strategic decisions of the military and political leadership of the country. Objective assessment of commissariats effectiveness were the results of their operations in wartime. From this point of view it is necessary to ascertain performance of its mission - to supply front with modern means of warfare. Largely due to this fact, the Soviet Union won in serious confrontation with the military-industrial complex military industry of Nazi Germany and its satellites. On the basis of archival documents and testimony of contemporaries the article shows the contribution of the defense industry in the Soviet Union's victory in the Great Patriotic War.